SAS Pro: an integrated mobile tool for strawberry disease control and multifungicide resistance strategies - Andreis, José Henrique Debastiani (2018)
Disease management is an important component in strawberry production worldwide. There has beenthe need for more efficient use of agrochemicals in specialty crops production, while also minimizingrisks of resistance development in target pathogens. This project presents the development of a platform and mobile application (SAS Pro), that integrates disease infection models, on-field spray reports, and fungicide resistance management guidelines aiming to provide more specific product and spraying recommendations, as well as, reduce selection forresistance on target pathogens, by automatically managing restrictions of fungicide use per application,season, and chemical class.